The moderating role of problem solving in Black-White marriages: a common fate model - Dominguez, María Mercedes (Kansas State University, 2017)
Black-White couples have the highest rate of divorce compared to other interracial pairings in the U.S. (Zhang & Hook, 2009). Given the racial climate in the United States that privileges White people (Burton et al., 2010; Hardy & Laszloffy, 2008; Killian, 2012), and the on-going opposition to Black-White unions (Pew Research Center, 2017), it is reasonable to expect that Black-White couples experience elevated stress from direct and indirect forms of racial discrimination. In order to identify factors that may help boost the resilience of non- divorced Black-White couples, this study used the Vulnerability Stress Adaptation (VSA) model of marriage (Karney & Bradbury, 1995) to better understand how problem-solving skills may buffer the impact of racial discrimination experienced by Black-White couples on marital satisfaction. The study included 178 Black-White heterosexual couples between the ages of 18 and 40. A common fate moderation analysis investigated whether problem-solving served as a mechanism through which Black-White couples were able to cultivate marital satisfaction despite the detrimental outcomes of discrimination experienced as an interracial couple. Results indicated that experiences of couple discrimination were negatively related to marital satisfaction and that couples’ problem-solving skills buffered the extent discrimination impacted couples’ marital satisfaction. The results have implications for therapists working with Black-White couples whether married or intending to marry. Research should further explore the impact discrimination experienced by interracial couples has on other aspects of relationships as well as on mental and physical health.
Keywords: Problem solving; Interracial couple; DiscriminationModeration